Integrating Halal and Thayyib Principles into Global Logistics Operation: A Comparative Analysis in Malaysia, UAE, and Indonesia - Yunanto, Dwi; Amalia, Euis; Saharuddin, Desmadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This paper examines how the concepts of halal and thayyib have evolved from basic religious dietary laws to broader principles guiding global industry practices. It explores how these principles are integrated into halal logistics systems in Malaysia, the UAE, and Indonesia. While Malaysia and the UAE have well-developed halal logistics systems, Indonesia is working to strengthen its own through regulations like Law No. 33 of 2014. However, challenges remain in Indonesia, including industry misunderstanding, infrastructure limitations, and regulatory delays. A real challenge is the postponement of the implementation of halal certification requirements until further notice, which was originally scheduled to start in October 2024. This qualitative study uses comparative analysis, literature reviews, and expert interviews to understand these challenges and proposes using ICT to improve halal logistics. The study's novelties include a comprehensive comparative analysis of halal logistics implementation across three countries, the integration of the conceptualization of halal and thayyib in Islam with halal value chain theory and institutional theory, and the emphasis on ICT's role in enhancing logistics efficiency. The study concludes that success in halal logistics requires coordinated efforts from policymakers, industry players, and technological advancements.